Disfigured: A Saudi Woman’s Story of Triumph over Violence By Rania Al-Baz (tr. Catherine Spencer) (Northampton, MA: Olive Branch Press, 2009. 160 pages.) (American Journal of Islam and Society, 2010)
Rania Al-Baz’s ten-chapter book touches on a sore point found all over theglobe and among people of all socioeconomic classes. Written in the first person,she intersperses her story with reports on the laws and customs in Islamand in Saudi society that shed light on the events in her life. The readerbecomes acquainted with her life philosophy, which helped her overcome thedifficulties she faced and the physical and mental pain she endured. Throughher personal story we learn how Arabs perceive relations between the sexes,Saudi women’s place in society and the home, women’s absolute submissionto their husbands and their desires, and the Qur’anic law concerning suchcrimes as murder (p. 8) and the physical abuse of women ...